Radiological and functional outcome post fixation in unstable proximal femur fracture: comparison between proximal femoral nail antirotation (PFNA) and proximal femoral locking compression plate (PFLCP) - Mohd Rashid, Zaraihah; MN, Nurhafizah; Y, Shukri; Mohd Yusof, Nazri (Malaysian Orthopaedic Association, 2019)
INTRODUCTION: Incidence of unstable proximal femoral fracture is increasing in trend and the treatment is challenging. Operative treatment offers various selection of implant including plate and intramedullary nail. The purpose of this study is to compare radiological and functional outcome between both implants: PFNA and PFLCP. METHODS: This is a single centre observational cohort study involving all patients with unstable proximal femur fracture, admitted from January 2012 till December 2017. Plain pelvic and hip radiographs at immediate, 6 month and 1 year post-operative. Neck shaft angle (NSA) and its difference on contralateral side measured. Radiological outcome evaluated prevalence of varus malalignment and quality of fracture reduction. Functional outcome is measured by using Lower Extremity Functional Scale (LEFS). RESULTS: Sample population is 91 patients. Radiological and functional outcome didn’t differ significantly (p>0.05) but PFLCP group had shown significant shorter union time (table 1,2). DISCUSSIONS: Association of radiological and functional outcome between both implants was statistically insignificant (p>0.05), which concurrent with the study by Singh AK, 2017, Li GX, 2012. CONCLUSION: Both implants were effective in treating unstable proximal femur fractures. REFERENCES: 1. Singh AK et al.Treatment of Unstable Trochanteric Femur Fracture:PFNA versus PFLCP. Am. Journal. 2017.